Online Salon Appointment and Management System of FOREVER18 Hair Salon - Khoo, Khoo Zi Xuan; Nurul Aswa Omar (Applied Information Technology And Computer Science, 2024)
The beauty and salon industry are evolving rapidly and customer convenience and salon management system has become paramount. Currently, FOREVER18 Hair Salon relies on the manual appointment system. This reliance on a manual appointment system leads to scheduling conflicts, inefficiencies and challenges in managing customer preferences, highlighting the need for a more streamlined and automated solution at FOREVER18 Hair Salon. Customers typically call the salon to schedule appointments which are recorded in a physical appointment book. Online Salon Appointment and Management System of FOREVER18 Hair Salon is developed to streamline the operations, improve customer experiences and enhance salon efficiency. The methodology for this proposed system is using the waterfall model. The HTML, CSS and JavaScript will be used for creating the user-friendly front- end interface for the customers. The PHP will be used for the back-end functionality and MySQL will be used as the database system with phpMyAdmin is selected as the web-based tool that is connected to the database system. The proposed system is applied in web-based platforms that indicates the functionality and features of Online Salon Appointment and Management System of FOREVER18 Hair Salon is accessible through a web browser which allows the users which are customer and administrator can interact with the system online. The expected result of the proposed system is that customers can register accounts on the FOREVER18 Hair Salon website which allows the customer to book appointments. On the administrator side, the proposed system allows administrators to manage appointments, services, customer information and generates the invoices and sales reports.